2022
DOI: 10.1021/acs.langmuir.2c00647
|View full text |Cite
|
Sign up to set email alerts
|

Dual-Sensing, Stretchable, Fatigue-Resistant, Adhesive, and Conductive Hydrogels Used as Flexible Sensors for Human Motion Monitoring

Abstract: Hydrogel-based sensors serve as an ideal platform for developing personalized wearable electronics due to their high flexibility and conformability. However, the weak stretchability and inferior conductivity of hydrogels have severely restricted their large-scale application. Herein, a natural polymer-based conductive hydrogel integrated with favorable mechanical properties, good adhesive performance, and excellent fatigue resistance was fabricated via interpenetrating tannic acid (TA) into a chitosan (CS) cro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 41 publications
(26 citation statements)
references
References 40 publications
0
25
0
Order By: Relevance
“…These results indicated that the as-prepared κ-CG/p­(HEMA-AA-AAm)/Al 3+ organohydrogels possess excellent self-adhesive function, which could effectively eliminate the interface gap between the substrate and organohydrogel in sensing tests and ensure that the various mechanical deformations were accurately translated into electronic signals. The adhesion mechanism may ascribe to the existing vast carboxyl and amino groups in organohydrogels that can form strong noncovalent bond interactions with functional groups on the various material surfaces (Figure f). Moreover, due to the high transparency of κ-CG/p­(HEMA-AA-AAm)/Al 3+ organohydrogels in the wavelength range of 400–700 nm, the picture behind the organohydrogel film could be clearly observed (Figure g). The outstanding optical transparency provides potential feasibility for the design of visual flexible sensors and electronics.…”
Section: Resultsmentioning
confidence: 99%
“…These results indicated that the as-prepared κ-CG/p­(HEMA-AA-AAm)/Al 3+ organohydrogels possess excellent self-adhesive function, which could effectively eliminate the interface gap between the substrate and organohydrogel in sensing tests and ensure that the various mechanical deformations were accurately translated into electronic signals. The adhesion mechanism may ascribe to the existing vast carboxyl and amino groups in organohydrogels that can form strong noncovalent bond interactions with functional groups on the various material surfaces (Figure f). Moreover, due to the high transparency of κ-CG/p­(HEMA-AA-AAm)/Al 3+ organohydrogels in the wavelength range of 400–700 nm, the picture behind the organohydrogel film could be clearly observed (Figure g). The outstanding optical transparency provides potential feasibility for the design of visual flexible sensors and electronics.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, it is an optimal choice to effectively combine the breath analysis technology with wearable devices . A wearable sensor is a real-time, non-invasive, and automatic monitoring device of human physiological parameters. …”
Section: Introductionmentioning
confidence: 99%
“…Strain sensors based on hydrogel flexibility can monitor human health in real time by sensing the body’s breathing, heartbeat, external vibration, and body temperature and converting them into visual electrical signals, demonstrating its great potential for applications in human–computer interaction, artificial sensor skin, and flexible sensors. , Conductive hydrogels with excellent mechanical flexibility, strain sensitivity, long-term stable sensing, and multistimulus responsiveness are candidates for the manufacture of strain sensors. However, the poor mechanical properties of hydrogels are due to their small internal forces and difficulty in energy dissipation .…”
Section: Introductionmentioning
confidence: 99%